Jacob : unexpected patriarch - Zakovitch, Yair (Jewish lives (New Haven, Conn.), 2012)
A powerful hero of the Bible, Jacob is also one of its most complex figures. Bible stories recounting his life often expose his deception, lies, and greed--then, puzzlingly, attempt to justify them. In this book, eminent biblical scholar Yair Zakovitch presents a complete view of the patriarch, first examining Jacob and his life story as presented in the Bible, then also reconstructing the stories that the Bible writers suppressed--tales that were well-known, perhaps, but incompatible with the image of Jacob they wanted to promote. Through a work of extraordinary "literary archaeology," Zakovitch explores the recesses of literary history, reaching back even to the stage of oral storytelling, to identify sources of Jacob's story that preceded the work of the Genesis writers. The biblical writers were skilled mosaic-makers, Zakovitch shows, and their achievement was to reshape diverse pre-biblical representations of Jacob in support of their emerging new religion and identity. As the author follows Jacob in his wanderings and revelations, his successes, disgraces, and disappointments, he also considers the religious and political environment in which the Bible was written, offering a powerful explication of early Judaism